2022
DOI: 10.1101/2022.03.13.484168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Life history diversity in a large group of chloroviruses

Abstract: Microbial viruses affect the ecology and evolution of every environment on earth. Although these effects can play out on a grand scale, to understand them we need to zoom in to virus' life cycle traits. The values of these traits determine a virus' effect on the host population, the trait diversity provides the material for natural selection, and trade-offs between the traits are expected to constrain virus' evolutionary potential. However, due to the difficulty involved in measuring viral life history phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
(323 reference statements)
0
3
0
Order By: Relevance
“…ii) the faster a plaque increases, the faster the virus spreads and iii) the larger the plaque becomes, the stronger the infection is. However, liquid infection assays where host and virus traits are usually identified [48] are needed to validate these assumptions. All of the mentioned characteristics of the infection will affect the infection dynamics within the ecosystem [10] and potential effects on the Ostreococcus populations [49].…”
Section: Discussionmentioning
confidence: 99%
“…ii) the faster a plaque increases, the faster the virus spreads and iii) the larger the plaque becomes, the stronger the infection is. However, liquid infection assays where host and virus traits are usually identified [48] are needed to validate these assumptions. All of the mentioned characteristics of the infection will affect the infection dynamics within the ecosystem [10] and potential effects on the Ostreococcus populations [49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiplex ddPCR can be used for exploring evolutionary changes, such as the evolution of virulence or resistance in the interaction between giant virus and virophage over time. Specifically, different isolated populations of giant virus and virophage stemming from different time points or locations of sampling, can be used to assess how giant virus-virophage interaction changed (i.e., quantifying and comparing virion production from combinations of different isolates) [ 3 ], such as is done using flow cytometry for assaying virus life-history traits (e.g., [ 31 ]). In the context of experimental evolution studies, comparison of virus populations isolated from the experiments with ancestral populations (i.e., the virus population that was used to inoculate the experiments) permits measurement of the population average trait changes (e.g., [ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
“…There has been evidence that the viral impact on phytoplankton communities is influenced by temperature and sunlight exposure. Previous studies on viral decay found that viral decay rates increased with sunlight exposure (Noble and Fuhrman, 1997;Suttle and Chen, 1992;Lievens et al, 2022). There has also been evidence that the number of infected cells is higher in the absence of light (by night) than in the presence of light (Winter et al, 2004;Derelle et al, 2018), suggesting a connection between viral infection and irradiance.…”
mentioning
confidence: 97%